Caracterização e modelagem geológica 3d de reservatórios turbidíticos e seus impactos na produção de petróleo - Chaves, Otavio Leite (2020)
Over the years, with the improvement in high-resolution 3D-seismic data and extensive outcrop studies, the knowledge about turbidite channel deposits has considerably grown. Nevertheless, despite the technological and conceptual advances, the predictability of this kind of reservoir remains difficult, especially in exploration areas. The different types of stacking patterns and the variety of sediment fillings in these deposits generate internal heterogeneity that is difficult to identify with the limitation of hydrocarbon industry existing data. One way to analyze the connectivity of turbidity deposits, especially in zones with few drilled wells and without historical production data, is executing a formation test. In these type of reservoirs, 3D geological modelling and numeric simulation are tools that allow the realization of uncertainty analysis, varying the static geological parameters and the dynamic engineer ones, associated with production behavior in different existing scenarios. The objective of this paper is to evaluate the hydraulic communication degree of turbidity channel complexes in different stacking and filling scenarios, through numeric simulation of a formation test with constant production during a two hundred hours hydrocarbon-flow. The pattern alteration of turbidity channel deposits from a higher predominance of lateral migration to a greater vertical stacking made the confinement in these deposits to increase. The different occurrence of barrier scenarios generated smaller confinements, showing that in other to have a lot of influence in the hydraulic connectivity, the channel deposits must have very effective permeability barriers. The increase in permeability intensified the investigation range of the test, which found barriers more rapidly. The stacking pattern, along with the permeability variation, were the most influential factors in the results of the formation test.